Lithium titanate material, preparation method of lithium titanate material, negative pole piece, battery and electric equipment
Through the ball grinding and ultrasonic treatment of lithium titanate raw materials, its granular distribution is adjusted, the problem of low density density of lithium titanate battery chip polar chip has been solved, and the energy density of lithium titanate battery has a significant improvement.
Patent Information
- Application Number
- CN202411272160.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-21
AI Technical Summary
The energy density of existing lithium titanate batteries is low, mainly due to the spherical structure of lithium titanate materials, the compaction density of the electrode sheet is relatively low, and the battery space cannot be fully utilized.
By ball milling the lithium titanate raw material, adjusting its particle size distribution so that the D50 after ball milling is 0.1-0.2 μm, and using ultrasonic treatment to make the D50 ≤ 1 μm, forming a bimodal particle size distribution structure, thereby improving the lithium titanate material. of compacted density.
The compacted density of lithium titanate battery pole pieces is significantly increased from 1.9g/cc to 2.4-2.6g/cc, thereby increasing the energy density of lithium titanate batteries.
Smart Images

Figure CN119330393A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a lithium titanate material and a preparation method thereof, as well as a negative electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium titanate material is a "zero strain" negative electrode material with many advantages such as fast charging and discharging, high safety, wide temperature resistance, and long cycle life. However, due to its low theoretical capacity and high cost, the energy density of the battery is low, which limits the commercial application of lithium titanate material. Therefore, improving the energy density of lithium titanate batteries is a very meaningful task.
[0003] The conventional lithium titanate material has a spherical pure phase lithium titanate material in its microscopic morphology. During the battery preparation process, there will be gaps between the spherical lithium titanate materials used as negative electrode materials that cannot be filled. The compaction density after coating is low, and the energy density of the battery will also be correspondingly low. Therefore, increasing the compaction density of the lithium titanate pole piece can reduce the thickness of the pole piece, increase the possibility of capacity compensation within the limited battery space, and thereby achieve the purpose of improving the energy density of the lithium titanate battery. Summary of the invention
[0004] In view of this, the purpose of the present application is to provide a lithium titanate material and a preparation method thereof, so that after the prepared lithium titanate negative electrode material is made into a negative electrode sheet, the compaction density of the lithium titanate battery sheet can be effectively improved, thereby achieving the purpose of improving the energy density of the lithium titanate battery;
[0005] Another object of the present application is to provide a negative electrode sheet, a battery and an electrical device based on the above-mentioned lithium titanate material.
[0006] In order to solve the above technical problem / achieve the above purpose or at least partially solve the above technical problem / achieve the above purpose, as a first aspect of the present application, a method for preparing a lithium titanate material is provided, comprising:
[0007] Obtaining lithium titanate raw materials;
[0008] The lithium titanate raw material is ball-milled to a slurry D 50 At 0.1-0.2μm, D 90 ≥10×D 50 , obtaining the ball milling slurry;
[0009] The ball mill slurry is processed to obtain a dry powder, and the powder is sintered to obtain the lithium titanate material.
[0010] Optionally, the ball milling is performed according to the following conditions:
[0011] The grinding medium is zirconia balls with a diameter of 0.35-0.5 mm and a filling rate of 70-80%; the solid content of the ball mill slurry is 10-15%.
[0012] Optionally, the sintering temperature is 600-700°C.
[0013] Optionally, the lithium titanate raw material is a lithium titanate raw material obtained by sintering lithium source and titanium source raw materials once.
[0014] As a second aspect of the present application, a lithium titanate material prepared by the preparation method described in the present application is provided, wherein the lithium titanate material has a D 50 At 7-10 μm, the particle size distribution has a single peak structure; after ultrasonic treatment, D50≤1 μm, the particle size distribution has a double peak structure.
[0015] As a third aspect of the present application, a negative electrode plate is provided, comprising a current collector and a negative electrode active material coated on at least one surface of the current collector; the negative electrode active material comprises the lithium titanate material described in the present application.
[0016] As a fourth aspect of the present application, a battery is provided, comprising the negative electrode plate described in the present application.
[0017] As a fifth aspect of the present application, there is provided an electrical device comprising the battery described in the present application.
[0018] The present invention prepares a lithium titanate material with significant particle size difference, and the material characteristics are specifically reflected in the significant D before and after ultrasonic treatment. 10 , D 50 , D 90 , D 99 The difference is reflected in the particle size distribution morphology, which is specifically reflected in the single-peak distribution structure of the particle size before ultrasonic treatment, and the bimodal distribution structure of the particle size after ultrasonic treatment. After the lithium titanate material prepared by the preparation method of the present application is made into a negative electrode, the compaction density of the lithium titanate battery electrode can be effectively improved from 1.9g / cc of conventional lithium titanate to 2.4-2.6g / cc, thereby achieving the purpose of improving the energy density of the lithium titanate battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application.
[0020] Figure 1 Shown is the SEM image of the "unstable stacking" of spherical lithium titanate after ball milling and spray drying in this application;
[0021] Figure 2 Shown is the SEM image of spherical lithium titanate after conventional one-time sintering;
[0022] Figure 3 The particle size distribution diagram of the lithium titanate material described in this application before and after ultrasound is shown;
[0023] Figure 4 Shown is the particle size distribution diagram of lithium titanate raw material before and after ultrasound after conventional primary sintering. DETAILED DESCRIPTION
[0024] The present application discloses a lithium titanate material and a preparation method thereof, as well as a negative electrode plate, a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0025] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.
[0026] In view of the problem that the compaction density of the battery pole piece prepared by conventional primary sintering lithium titanate raw materials is too low, the present invention performs secondary treatment on the primary sintering lithium titanate raw materials to make them have significant particle size differences and have a lower particle size D after ultrasonic treatment. 50≤1μm, ensuring that the material is relatively easier to roll after coating the pole piece. At the same time, it has a double-peak structure in the particle size distribution morphology. Particles with different sizes can play a filling role, which is also beneficial to the improvement of the compaction of the material pole piece.
[0027] In a first aspect of the present application, a method for preparing a lithium titanate material is provided, comprising:
[0028] Obtaining lithium titanate raw materials;
[0029] The lithium titanate raw material is ball-milled to a slurry D 50 At 0.1-0.2μm, D 90 ≥10×D 50 , the ball-milled slurry is obtained, and the specific surface area of the slurry after ball milling is 3-30m 2 / g;
[0030] The ball mill slurry is processed, for example, spray-dried to obtain dry powder, and the powder is sintered to obtain the lithium titanate material.
[0031] During the ball milling process, control the ball milling slurry D 50 At 0.1-0.2μm, D 90 Value ≥ 10 × D 50 The value is then used to make the single crystal particles of lithium titanate material after ball milling form an "unstable stacking" effect after spray drying. This unstable stacking refers to the use of single crystal particles of different sizes with significant size differences to stack or connect into a whole, which is difficult to form a stable structure. The SEM picture is shown in Figure 1 The secondary spherical phase formed by lithium titanate single crystal particles with similar particle size is more stable (its D 50 At 0.1-0.2 μm, D 90 The value is 0.2-0.5μm, SEM picture is shown in Figure 2 ). This unstable state can help fill the gaps between spherical lithium titanate materials when preparing negative electrode sheets, thereby significantly improving their compaction density.
[0032] In certain embodiments of the present application, the ball milling time, zirconium ball filling rate, zirconium ball size, solid content, etc. are controlled to ensure that the lithium titanate D after ball milling is 50 Meet the requirements, and refer to the following conditions for ball milling:
[0033] The grinding medium is zirconia balls with a diameter of 0.35-0.5 mm and a filling rate of 70-80%; the solid content of the ball milling slurry is 10-15%, and the ball milling time is generally 1-120 minutes.
[0034] In certain embodiments of the present application, the sintering temperature is 600-700°C, such as 660°C, 670°C, etc.
[0035] In some embodiments of the present application, the lithium titanate raw material is a lithium titanate raw material obtained by sintering a lithium source and a titanium source raw material once. The lithium source and the titanium source raw material can be any lithium-containing material and titanium-containing material that can be used to prepare lithium titanate, such as lithium hydroxide, titanium dioxide, etc.; in some other embodiments of the present application, the process for preparing the lithium titanate raw material by sintering once includes:
[0036] The lithium source and titanium source raw materials are weighed according to the stoichiometric ratio, and ultrapure water is used as the dispersion medium for cyclic stirring. After the stirring is completed, spray drying is performed and sintering is performed at 400-800°C to obtain a primary sintered lithium titanate raw material, the particle size of which is generally 8-12μm.
[0037] In the second aspect of the present application, a lithium titanate material prepared by the preparation method described in the present application is provided, wherein the specific surface area of the material is 3-20 m 2 / g; D of the lithium titanate material before ultrasonic treatment 50 At 7-12μm, the particle size distribution has a single peak structure; after ultrasonic treatment, D50≤1μm, the particle size distribution has a double peak structure. The particle size distribution morphology is shown in the figure. Figure 3 The particle size distribution morphology of the lithium titanate raw material obtained by conventional one-time sintering shows that no significant change is observed in its particle size distribution morphology, whether ultrasonic treatment is performed or not, and it still has a single peak structure. Figure 4 .
[0038] In a third aspect of the present application, a lithium titanate negative electrode plate is provided, comprising a current collector and a negative electrode active material coated on at least one surface of the current collector; the negative electrode active material comprises the lithium titanate material described in the present application.
[0039] In certain embodiments of the present application, the negative electrode active material further includes a binder and a conductive agent, and the mass percentage of the lithium titanate material: conductive agent: binder is 90-98%: 1-5%: 1-5%. The conductive agent includes but is not limited to one or more of carbon black conductive agents, graphene conductive agents and carbon fiber conductive agents. Carbon black conductive agents include conductive carbon black SP, Ketjen black and acetylene black, etc. The binder includes PVDF, PAA, SBR, CMC, etc.
[0040] In the process of preparing the negative electrode sheet, the negative electrode active material is mixed with a solvent such as water or NMP to form a negative electrode slurry with a certain viscosity, and the negative electrode slurry is coated on a current collector with good conductivity such as copper foil and aluminum foil to form a uniform negative electrode layer. Then, it is dried in a constant temperature drying oven to remove moisture and solvent in the negative electrode layer. The dried negative electrode sheet is roller-pressed to increase its density and compactness. Then, the negative electrode sheet is cut according to the battery design requirements to obtain a negative electrode sheet that meets the requirements.
[0041] In a fourth aspect of the present application, a battery is provided, comprising the negative electrode plate described in the present application.
[0042] In certain embodiments of the present application, it can be a lithium-ion battery, including a positive electrode plate, a separator, an electrolyte, and the negative electrode plate described in the present application. The positive electrode active material of the positive electrode plate includes but is not limited to lithium manganese oxide, ternary materials or lithium iron phosphate, and the preparation process of the positive electrode plate can refer to the negative electrode plate.
[0043] In certain embodiments of the present application, the lithium-ion battery includes but is not limited to a soft-pack battery, a button battery, a square-shell battery, a half-battery or a full battery, etc.
[0044] In a fourth aspect of the present application, an electric device is provided, comprising the lithium-ion battery described in the present application, wherein the lithium-ion battery provides electric energy for the electric device. The electric device may be various devices driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.
[0045] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.
[0046] The following is a further description of a lithium titanate material and a preparation method thereof, as well as a negative electrode plate, a battery and an electrical device provided in the present application.
[0047] Embodiment 1:
[0048] Lithium hydroxide and anatase titanium dioxide are used as raw materials to prepare a primary sintered lithium titanate raw material, wherein Li is in excess of 2.5% mol relative to the stoichiometric ratio of Ti. Ultrapure water is used as the dispersion medium, and the above two raw materials are circulated and stirred in a reactor for 6 hours at a stirring rate of 300 rpm. After the stirring is completed, spray drying is performed and sintering is performed at about 600°C to obtain a primary sintered lithium titanate material with a particle size of 8-12μm.
[0049] The lithium titanate raw material is subjected to ball milling treatment, and the ball mill used is a horizontal ball mill. The zirconium ball filling rate is 70-80%, the unit power of ball milling is 0.35kWh / kg, the grinding medium is zirconium oxide ball, the diameter of the zirconium ball used is 0.35-0.5mm, and the ball milling method is continuous ball milling. The solid content of the ball milling slurry is 10%, and the particle size after ball milling is D 50 At 0.15μm, D 90 The particle size of the slurry after ball milling is 1.79 μm (>10×0.15 μm), and the particle size of the slurry after ball milling is 12 μm. 2 / g, the viscosity of the slurry after ball milling is about 300mps. The particle size test of the slurry after ball milling is shown in Table 1 below;
[0050] Table 1
[0051]
[0052] The slurry was spray dried, and the spray dried powder was sintered at 660°C with a heating rate of 10°C / min and kept warm for 1.5h to obtain the formed lithium titanate material. 50 At 10.59μm, the material exceeds D 50 The material ratio is 0.95μm and the material ratio is 7.20m 2 / g, see Table 2 below;
[0053] Table 2
[0054]
[0055] The formed lithium titanate material was used to mix PVDF and carbon black (96%:2%:2%) in proportion to prepare a lithium titanate negative electrode sheet. The lithium titanate negative electrode sheet was compacted to obtain a sheet weight of 2.45 g / cc under a pressure of 300 bar.
[0056] Embodiment 2:
[0057] The lithium titanate raw material sintered once in Example 1 was subjected to ball milling treatment, and the ball mill used was a horizontal ball mill. The zirconium ball filling rate was 70-80%, the unit power of ball milling was 0.50 kWh / kg, the grinding medium was zirconium oxide balls, the diameter of the zirconium balls used was 0.35-0.5 mm, and the ball milling method was continuous ball milling. The solid content of the ball milling slurry was 10%, and the particle size after ball milling was D 50 At 0.17μm, D 90 is 1.99μm (>10×0.17μm), and the slurry ratio after ball milling is 19m 2 / g, the viscosity of the slurry after ball milling is about 300mps. The particle size test of the slurry after ball milling is shown in Table 3 below;
[0058] Table 3
[0059]
[0060] The slurry was spray dried, and the spray dried powder was sintered at 670°C with a heating rate of 10°C / min and kept warm for 1.5h to obtain the formed lithium titanate material. 50 At 10.48μm, the material exceeds D 50 The material ratio is 0.89μm and the material ratio is 7.20m 2 / g, see Table 4 below;
[0061] Table 4
[0062]
[0063] The formed lithium titanate material was used to mix PVDF and carbon black (96%:2%:2%) in proportion to prepare a lithium titanate negative electrode sheet. The lithium titanate negative electrode sheet was compacted to obtain a sheet weight of 2.40 g / cc under a pressure of 300 bar.
[0064] Embodiment 3:
[0065] The lithium titanate raw material sintered once in Example 1 was subjected to ball milling treatment, and the ball mill used was a horizontal ball mill. The zirconium ball filling rate was 70-80%, the unit power of ball milling was 0.10 kWh / kg, the grinding medium was zirconium oxide balls, the diameter of the zirconium balls used was 0.35-0.5 mm, and the ball milling method was continuous ball milling. The solid content of the ball milling slurry was 10%, and the particle size after ball milling was D 50 At 0.12μm, D 90 is 1.32μm (>10×0.12μm), and the slurry ratio after ball milling is 12m 2 / g, the viscosity of the slurry after ball milling is about 300mps. The particle size test of the slurry after ball milling is shown in Table 5 below;
[0066] Table 5
[0067]
[0068] The slurry was spray dried, and the spray dried powder was sintered at 660°C with a heating rate of 10°C / min and kept warm for 1.5h to obtain the formed lithium titanate material. 50 At 11.51μm, the material exceeds D 50 The material ratio is 0.99μm and the material ratio is 7.35μm 2 / g, see Table 6 below;
[0069] Table 6
[0070]
[0071] The formed lithium titanate material was used to mix PVDF and carbon black (96%:2%:2%) in proportion to prepare a lithium titanate negative electrode sheet. The lithium titanate negative electrode sheet was compacted to obtain a sheet weight of 2.60 g / cc under a pressure of 300 bar.
[0072] Comparative Example 1:
[0073] The lithium titanate raw material sintered once in Example 1 is directly used, and PVDF and carbon black (96%: 2%: 2%) are mixed in proportion to prepare a lithium titanate negative electrode plate. The lithium titanate negative electrode plate obtains a plate compaction of 1.9g / cc under a pressure of 300bar. The 2.4-2.6g / cc plate compaction of Examples 1 to 3 of the present application is increased by 26.3%-36.8% compared to the plate compaction of Comparative Example 1. The significant improvement in the plate compaction can reduce the thickness of the plate, increase the capacity within the limited battery space, and thus achieve the purpose of improving the energy density of the lithium titanate battery.
[0074] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a lithium titanate material, characterized in that: include: Obtaining lithium titanate raw materials; The lithium titanate raw material is ball-milled to a slurry D 50 At 0.1-0.2μm, D 90 ≥10×D 50 , obtaining the ball milling slurry; The ball mill slurry is processed to obtain a dry powder, and the powder is sintered to obtain the lithium titanate material.
2. The preparation method according to claim 1, characterized in that: The ball milling is carried out according to the following conditions: The grinding medium is zirconia balls with a diameter of 0.35-0.5 mm and a filling rate of 70-80%; the solid content of the ball mill slurry is 10-15%.
3. The preparation method according to claim 1, characterized in that: The sintering temperature is 600-700°C.
4. The preparation method according to claim 1, characterized in that: The lithium titanate raw material is obtained by sintering lithium source and titanium source raw materials once.
5. The lithium titanate material prepared by the preparation method according to any one of claims 1 to 4, characterized in that: The D of the lithium titanate material before ultrasonic treatment 50 At 7-12 μm, the particle size distribution has a single peak structure; after ultrasonic treatment, D50≤1 μm, the particle size distribution has a double peak structure.
6. A negative electrode plate, characterized in that: It comprises a current collector and a negative electrode active material coated on at least one surface of the current collector; the negative electrode active material comprises the lithium titanate material according to claim 5.
7. A battery, characterized in that: Including the negative electrode sheet as described in claim 5.
8. An electrical device, characterized in that: Comprising the battery as claimed in claim 7.